Case Report: Novel mutations in two patients with MED13L-related intellectual disability highlighting the importance of genetic counseling - Cao, Hanyu; He, Tiantian; Wang, Jing; Zhou, Cong; Wei, Xing; Zhang, Xuemei (Frontiers in Genetics, 2025)
MED13L-related intellectual disability (ID) (impaired intellectual development and distinctive facial features with or without cardiac defects, OMIM: 616789) is a neurodevelopmental condition characterized by intellectual disability, hypotonia, motor delay, and remarkable speech delay. We report two novel cases, each harboring a novel pathogenic MED13L variant, who presented with additional, previously unreported features: oligospermia in a 32-year-old male proband and oligohydramnios and hematuria in a 6-year-old female proband, thereby expanding the known phenotypic spectrum. The study underscores the value of genetic testing and counseling, exemplified by the successful prenatal diagnosis and birth of an unaffected child in the second family. In addition, we reviewed previous literature with respect to phenotypic and genetic information. The literature reviewed here may potentially provide information for assessing clinical symptoms and genetic counseling. This study also highlights the importance of preconception genetic counseling for couples with suspected genetic disease.